Characterization of Acrocarpus fraxinifolius wood submitted to heat treatment - Carolina A. Barros Oliveira; Karina A. de Oliveira; Vinicius Borges de Moura Aquino; André Luis Christoforo; Julio C. Molina (Maderas: Ciencia y Tecnología, 2022)
Aiming to provide greater visibility for the wood species Acrocarpus fraxinifolius, the present study sought to analyze the influence of heat treatment on an industrial scale applied to wood species, also popularly known as Indian cedar. The heat treatment was carried out in an autoclave, with temperature and pressure control, and with saturated steam injection, for temperatures 155 ºC, 165 ºC, 175 ºC, and 185 ºC. Physical, chemical, and mechanical tests were carried out for the analyzed wood. The content of holocellulose and total lignin decreased, while the content of extractives showed a substantial increase. The density increased after the heat treatment, however the treated wood showed cracks, and these cracks influenced the significant loss of the values of the mechanical properties of compression, tension, and flexion. The shear showed strength gain for the temperature of 155 ºC, and the wood treated at 165 ºC was equivalent to untreated wood. The woods submitted to temperatures of 175 ºC and 185 ºC presented strength losses. The heat treatment in question contributes to increase the visibility, use and market value of wood.